THE EFFECT OF ANNEALING TEMPERATURES AFTER THERMOMECHANICAL PROCESS TO THE CORROSION BEHAVIOR OF Ni3(Si,Ti) IN SULFATE SOLUTION - Gadang Priyotomo; Yasuyuki Kaneno (International Journal of Science and Engineering, 2015)
The corrosion behaviour of the intermetallic compounds Ni3(Si,Ti) (L12: single phase), has been investigated using an immersion test, polarization method, scanning electron microscope in 0.5 kmol/m3 H2SO4 solution at 303 K.  Moreover, the corrosion behaviour of austenitic stainless steel type 304 was studied under the same experimental conditions as reference. It was found that the intergranular attack and uniform attack were observed on Ni3(Si,Ti) after thermomechanical and annealing processes (1173K and 1273K) respectively in the immersion test. From the immersion test and polarization curves, all annealed Ni3(Si,Ti) had less corrosion resistance compared to type 304. In addition, Ni3(Si,Ti) was difficult to form a stable passive film, but not for type 304.